3D Printing/Additive Manufacturing Technologies in Dentistry: A Bibliometric Study - Terzi, Mithat; Tuğçe Bulut, Begum; Büyük, S. Kutalmış; Yavuz, Mustafa Cihan; Abay, Feridun (Current research in dental sciences (Online), 2025)
Objective: The aim of this study was to present a bibliometric analysis of scientific articles about the additive manufacturing technologies in dentistry. Method: The papers published until 24 July 2023, were searched in Web of Science. The top 50 articles with the highest citations and suitable for the study subject were selected among the totally 604 articles. Results: The United States positioned first in the number of articles with a total of 13 articles. Most included articles were published in Journal of Prosthetic Dentistry (n=8), Dental Materials (n=6), Journal of Prosthodontics-Implant Esthetic and Reconstructive Dentistry (n=5), and Materials (n=4). The most cited article was published in 2019 and the number of citations in Web of Science was 194. Conclusion: Additive manufacturing research presents a dynamic environment and is estimated to stay presenting high productivity and broad application in the future dentistry.